2021
DOI: 10.1002/ajh.26230
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline treatment, cardiovascular risk factors and the cumulative incidence of cardiovascular disease in a cohort of newly diagnosed lymphoma patients from the modern treatment era

Abstract: The development of cardiovascular disease (CVD) in long-term survivors of lymphoma is of increasing importance. Here, we characterize the cumulative incidence and risk factors for CVD in lymphoma patients diagnosed in the current treatment era. From 2002-2015, newly diagnosed lymphoma patients (>18 years) were enrollment into a prospective cohort study that captured incident CVD, consisting of congestive heart failure (CHF), acute coronary syndrome (ACS), valvular heart disease (VHD), and arrhythmia. The cumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Interestingly, radiation therapy to the chest and mediastinum did not emerge as an independent risk factor for CHF. Consistent with our study, a prospective cohort study of patients with newly diagnosed lymphoma found that patients had increased risk of cardiovascular disease, especially CHF, at 10 years, but receipt of radiation therapy was not associated with this outcome and this was also found in the study by Salz et al using a Danish registry cohort. However, not all chest radiation affects the heart to the same degree.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, radiation therapy to the chest and mediastinum did not emerge as an independent risk factor for CHF. Consistent with our study, a prospective cohort study of patients with newly diagnosed lymphoma found that patients had increased risk of cardiovascular disease, especially CHF, at 10 years, but receipt of radiation therapy was not associated with this outcome and this was also found in the study by Salz et al using a Danish registry cohort. However, not all chest radiation affects the heart to the same degree.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on validating disease endpoints and second‐primary cancers, while other health outcomes were self‐reported. However, with our access to medical records, LEO can validate other endpoints later, such as in the MER for cardiovascular disease 36 …”
Section: Discussionmentioning
confidence: 99%
“…36 While the LEO cohort has age, sex, racial/ethnic and geographic diversity, patients older than 80 years were underrepresented in the cohort relative to SEER data, as were Asian/Pacific Islanders. All LEO recruitment centers are academic medical centers with strong lymphoma clinical practices, and thus LEO will not be fully representative of community patients, although many participants enrolled at LEO centers are managed in the community.…”
mentioning
confidence: 99%
“…Anthracycline-induced cardiotoxicity is a growing challenge for public health, due to the ageing population with an increasing prevalence of cardiovascular risk factors and the widespread use of anthracyclines in lymphoma therapy, with high response rates and improved overall survival 14 . Our study reports incidence and risk factors for cardiotoxicity in a cohort of 200 lymphoma patients undergoing rst-line treatment with anthracyclines.…”
Section: Discussionmentioning
confidence: 99%